Quasi-hyperbolic discounting and externalities: Can government intervention improve wefare? - Christos Kotsogiannis; Robert Schwager (ZBW - Leibniz Information Centre for Economics, 2020)
The recent literature has emphasized that government intervention when consumers have quasi-hyperbolic preferences ('bias for the present') over consumption is not welfare-enhancing. This paper introduces a market imperfection (which takes the form of a negative externality) and shows that government intervention is welfare-enhancing if the market imperfection is sufficiently strong or the consumers' bias for the present is weak. This conclusion holds, interestingly, even if the gocernment and the consumers share the same biased intertemporal preferences.
Keywords: H23; D15; D9; 330; Quasi-hyperbolic preferences; optimal savings; bias for the present; time consistent policy; externalities